(untitled) (Bangladesh Journal of Zoology, 2021)
The knowledge on benthic fauna is important to know the biological interactions of the ecosystem. Abundance and composition of benthos along with some physico-chemical parameters of water of Rajdhalabeel, Netrokona was carried out from May 1998 to April 1999. The water parameters varied between or within the months but they did not vary from location to location. The benthic organisms had fluctuated both quantitatively and qualitatively. Considerable variation of benthos was detected during the period of the study. The composition of benthos were 38.26%, 29.86% and 25.22% for molluscs, oligochaetes and chironimids respectively. The highest number (1310.98 ind/m2) was recorded in July, 1998 while it was lowest (333.3 ind/m2) in April, 1999.The study revealed the beel as productive one and implementation of a little development work, good management and protect fishes from poaching may turn the beel into a very good fish resource. Bangladesh J. Zool. 49(1): 57-68, 2021